An SDN-IoT-based secure simulation system for smart cities. (19th November 2021) - Begum, Seema; Yao, Nianmin; Shah, Syed Bilal Hussain; Stephan, Thompson; Li, Xingwang
The massive spike in security threats is one of the greatest security problems facing the internet of things (IoT). Many IoT gadgets do not have any protection features, and even the ones they have are mostly primitive and can thus easily be subject to attacks. Compromising one or more infrastructure components will theoretically lead to the vulnerability of the IoT network's entire infrastructure. The software defined networking (SDN) poses many possibilities in this sense and offers the ability to address those difficulties. In this paper, the proposed solution may not resolve all the challenges; however, it overcomes a particular challenge concerning software defined networking (SDN) without any modification to the present network architecture. The proposed secure solution allows SDN to work as an integrated and programmable controller for smart cities. According to various studies, IoT and SDN's integration allows unlocking several routes that provide security and making smart cities a reality with SDN. The SDN-based IoT network is studied in this paper, and it further proposes an effective IoT-based security system with the help of SDN-IoT design.